B2B or Not to Be: Does B2B E-Commerce Increase Labour Productivity? - Irene Bertschek; Helmut Fryges; Ulrich Kaiser (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
We implement an endogeneous switching-regression model for labour productivity and firms' decision to use business-to-business (B2B) e-commerce. Our approach allows B2B usage to affect any parameter of the labour productivity equation and to properly take account of strategic complementarities between the input factors and B2B usage. Empirical evidence from 1,394 German firms shows that firms using B2B e-commerce have a significantly higher output elasticity with respect to ICT-investment and produce significantly more efficiently than firms that do not use B2B. Firms' labour productivity is enhanced by using B2B.
Keywords: C21; D24; 330; Business-to-business e-commerce; labour productivity; endogenous switching regression model; survey data; Lieferanten-Kunden-Beziehung; E-Business; Innovationswettbewerb; Arbeitsproduktivität; Schätzung; Deutschland